Preschool quality and women’s off-farm labor force participation: Evidence from China - Li, Shaoping; Liu, Chengfang; Chen, Kevin Z.; Luo, Renfu; Yu, Yanying; Wang, Xinyu (International Association of Agricultural Economists, 2021)
We study the impact of preschool quality on off-farm work participation among women. We first develop a theoretical model that predicts higher qualities of preschools increase the likelihood of women’s off-farm labor force participation. This prediction is then empirically verified by using data from rural China. Our results suggest that policies aimed at increasing the quality of preschools in rural China might help not only improve the education quality of preschool children but also increase women’s off-farm labor force participation, both of which are of great importance for China considering its aging population and growth model shifting from high-speed growth to high-quality development.